Integrating journalism and public health to promote training and education on global health reporting - Dr. H Fong, PhD; E Harris, PhD; D Tuller, DrPH (Elsevier, 2015)
Background: As the Ebola epidemic and other emerging diseases have shown, global health journalism has an influential role in public health action and inaction. Practical experience is important in preparing young people in ethical and technically accurate global health reporting. However, such training has not traditionally been incorporated into global public health education. The Center for Global Public Health at the University of California (UC), Berkeley, USA, was created in 2008 to foster global health research and education across the entire campus. Part of its aim is to foster transdisciplinary public health research and learning through global public health opportunities for students. Methods: In 2013, the UC Berkeley Center for Global Public Health and the UC Berkeley Graduate School of Journalism partnered to create a new global health reporting internship that enables both public health and journalism graduate students the opportunity to investigate issues related to health disparities and/or health equity in low-to-middle-income countries. The programme seeks to provide faculty mentoring and guidance for interns who want to gain on-the-ground experience in reporting on important global health issues in developing countries. The fellowship is offered annually via a competitive application process, and the first two recipients completed their internships in the summer of 2014. Findings: One Master of Public Health student explored migrant health and repatriation in Burundi, and a Master of Journalism student studied family planning in Burkina Faso. Their stories were printed or broadcasted through radio, print, and web media. They have also presented their work and talked about their experience at academic symposia and various media and online platforms. The students are now better prepared in their careers to share public health narratives on important global health issues. With the internship, they have also enriched their public health and journalism learning in their existing degree programmes. Interpretation: The positive response to the internship programme by all involved indicates a need to further the programme both at UC Berkeley and beyond. Such transdisciplinary internships and opportunities should be supported by not only traditional public health disciplines but also journalism programmes, especially as the numbers of global health centres and programmes flourish across the USA and elsewhere. Funding: UC Berkeley Center for Global Public Health/UC Berkeley School of Journalism